Effect of Biomass Feedstock Granulometry on Thermophysical Characteristics of Charcoal Briquettes via Screw Extrusion - Samsudin Anis; Jefri Bale; Septian Eko Cahyanto; Ninda Kurniadi; Deni Fajar Fitriyana; M. Thooriq Anwar; Januar Parlaungan Siregar; Natalino Fonseca Da Silva Guterres (Advance Sustainable Science Engineering and Technology, 2025)
The present study investigates the impact of particle size variation (10, 18, 20, and 35 mesh) on the physical and thermal properties of charcoal briquettes from coconut shells manufactured with a screw-based extruder machine. The briquette manufacturing process involves crushing, mixing, molding, and drying. Assessments were conducted to ascertain friability, compressive strength, density, calorific value, volatile matter, ash content, fixed carbon, and water content. Comparable assessments were also performed on commercially available export-grade briquettes designated as b_5. The results of this investigation demonstrate that all briquette samples generated conform to the SNI 01-6235-2000 standard for water, ash, and calorific value, and adhere to international standards for fixed carbon, density, and compressive strength. The b_4 specimen (35 mesh) demonstrated the best performance, exhibiting a friability of 0% in the unburned condition and 7.04% in the burned condition. Compared to b_5, the b_4 specimen exhibited notable enhancement, demonstrating a 100% increase in friability in the unburned condition and a 53.22% improvement in the burned condition. This study emphasizes the significance of smaller particle sizes in improving briquettes' mechanical strength and combustion efficiency. It presents the importance of renewable energy technology and sustainable waste management.